THE RIDERS FOR FRICTION PAIRS WITH FLUOROPLASTIC BASED COVER - V.A. KOHANOVSRY; U.A. PETROFF; M.A. MUKUTADZE; M.H. SERGHEEVA (Advanced Engineering Research, 2007)
Results of experimental investigations of the riders parameters considered. The riders contact with the samples covered by metal-fluoroplastic.